Jeffrey Johnson. Creative Development in Marcel Proust’s A la Recherche du Temps Perdu. New York: Peter Lang, 2012. xv + 230 pp. - Claudine Fisher (Studies in 20th & 21st Century Literature, 2014)
Review of Jeffrey Johnson. Creative Development in Marcel Proust’s A la recherche du temps perdu. New York: Peter Lang, 2012. xv + 230 pp.
Keywords: A la recherche du temps perdu; Marcel Proust